2019
DOI: 10.32598/irj.17.4.305
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Time Use Patterns and Self-Efficacy Between Mothers of Children With Cerebral Palsy and Mothers of Typically Developing Children

Abstract: Comparing time use patterns and self-efficacy in two groups of mothers, including mothers of children with Cerebral Palsy (CP) and mothers of children with typical development, is the main objective of this study. Methods: This study was carried out in 2017 in Arak, Iran, on 200 mothers. Multiple sources of the evaluation, including Mothers' Time Use Questionnaire and Sherer General Self-efficacy Questionnaire, were used. SPSS v. 22 software was used to analyze the data. Results: The Mean±SD age of children wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This finding may be a sign of what has been previously studied (Rassafiani et al, 2012), showing that mothers of children with CP spend more time on childcare than mothers of typically developing children, and this issue results in less time allocated to other occupations, with a corresponding decrease in satisfaction (Rassafiani et al, 2012). Researchers showed that mothers of children with CP performed different characteristics from mothers of typically developing children (Riyahi et al, 2019). Moreover, mothers of children with CP have been shown to face difficulty engaging in cooccupations because taking their children to various centers for treatment, rehabilitation, and education leave them little time for leisure activities (Dalvand et al, 2015).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This finding may be a sign of what has been previously studied (Rassafiani et al, 2012), showing that mothers of children with CP spend more time on childcare than mothers of typically developing children, and this issue results in less time allocated to other occupations, with a corresponding decrease in satisfaction (Rassafiani et al, 2012). Researchers showed that mothers of children with CP performed different characteristics from mothers of typically developing children (Riyahi et al, 2019). Moreover, mothers of children with CP have been shown to face difficulty engaging in cooccupations because taking their children to various centers for treatment, rehabilitation, and education leave them little time for leisure activities (Dalvand et al, 2015).…”
Section: Discussionmentioning
confidence: 69%
“…Mothers of children with CP spend more time on occupations related to their children than mothers of typically developing children (Rassafiani et al, 2012). Moreover, Riyahi et al (2019) showed that mothers of children with CP concentrate on resting/sleep and childcare and home occupations, while mothers of children with typical development focus on self-care, leisure, and work occupations.…”
Section: Introductionmentioning
confidence: 99%